Faktor-Faktor yang Mendorong Konsumen Membeli Produk Elzatta di TikTok Live Shopping: Perspektif Stimulus–Organism–Response Theory - Firliansa, Alek; Haryanto, Totok; Astuti, Herni Justiana; Endratno, Hermin (Jurnal Ilmiah Ekonomi Islam, 2025)
This research aims to examine how online customer reviews and interactive content marketing of Elzatta’s products during TikTok Live Shopping sessions influence consumer purchase decisions, using the Stimulus–Organism–Response (S-O-R) theory as a conceptual framework. In this model, purchase intention serves as a mediating variable between external stimuli (content marketing, customer reviews, and religiosity) and the behavioral response (purchase decision). The study involved 157 respondents, selected through purposive sampling, and data were collected via an online questionnaire targeting Elzatta consumers in Purwokerto who actively follow or purchase through TikTok live sessions. The analysis of the data utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS 4 software. The findings reveal that content marketing and purchase intention have a positive and significant effect on purchase decisions. However, online customer reviews show no significant influence, and religiosity demonstrates a negative impact on purchase decisions. Additionally, purchase intention does not mediate the effects of content marketing, customer reviews, or religiosity on purchase decisions, suggesting that direct factors such as personal values and perceived content quality play a more crucial role in shaping consumer behavior in this context.